رهانات المورد البشري لتطبيق إدارة المعرفة في المؤسسة الاقتصادية: دراسة حالة: مجمع الإخوة عموري للآجر الأحمر - حسيني، ابتسام (جامعة محمد خيضر بسكرة, 2017)
Giving more importance to the Human Element is the most important part to create a successful a Knowledge Management (KM) in organisation. The one tha plays an essenciel role in implimenting KM programs, This requires improving skills of employees through a continuous training, and rehabilitation, To be able to Accommodate the requirements of the shift toward KM. So, in this paper, We have noticed that The AMMOURI BROTHER’S COMPLEX for red brick, They could grab a market share that can not be underestimated due to the taken decisive decisions by the higher administration of the complex about the KM, The one that had big impact in the leadership and the expansion of the complex.
لكي تكون إدارة المعرفة ناجحة في المؤسسة لا بد من التفكير بأهم ركن فيها وهو العنصر البشري والذي يلعب دورا أساسيا في عملية التنفيذ لبرامج إدارة المعرفة وهذا يتطلب تطوير مهارات العاملين من خلال التدريب المستمر والتأهيل، ليتمكن من استيعاب متطلبات التحول إلى برامج إدارة المعرفة وفي هذا المقال نلاحظ ان مجمع الإخوة عموري للآجر الأحمر، قد استطاع الاستيلاء على حصة سوقية لا يستهان بها نظرا لتلك القرارات الحاسمة التي اتخذتها الإدارة العليا للمجمع في مجال ادارة المعرفة، والتي كان لها الأثر الكبير في ريادة المجمع وتوسعه.
Keywords: التدريبات المهنية -- رأس المال الفكري -- إدارة المعلومات